Contribution to the californian suppository test.- I. Hardness, melting temperature and melting time of IM / 8 monoleno suppositories - Ruiz, Mª.J.; Suñé, J.Mª. (Ars Pharmaceutica (Internet), 1968)
In this first communication studied the minimum number of tests have to make with suppositories, made with an oil-soluble excipient, Monolone IM/8, in order to obtain values of weight, consistency and time of fusion statistically acceptable, that is, representative of a population. At the same time, study the influence of time in storage in the result of these tests.